Latent profile analysis of nurses’ the quality of palliative nursing care - Dong, Xue; Liu, Yan; Fang, Kui; Wang, Zezhou (Frontiers in Medicine, 2025)
ObjectivesTo explore the status of nurses’ the quality of palliative nursing care, analyze the potential characteristics and influencing factors of different types of nurses’ the quality of palliative nursing care, and provide reference for formulating intervention programs of nurses’ the quality of palliative nursing care.MethodsA total of 316 nurses from three hospitals in Liaoning Province were selected by using convenience sampling method in April 2024. General information questionnaire, the Palliative Nursing Care Quality Scale (PNCQS), Meaning in Life Questionnaire, the Chinese version of the Bradley Attitude Assessment Questionnaire, and the Coping with Death Scale Short Version were used to investigate. SPSS 26.0 and Mplus 8.3 were used for data analysis.ResultsThe score of the quality of palliative nursing care was (3.76 ± 0.77), and two latent profiles were identified: the low-quality group and the high-quality group, accounting for 47% and 53%. Attitude of nurses toward palliative care, meaning in life, and coping with death competence were the factors influencing the potential categories of nurses’ the quality of palliative nursing care (P < 0.05).ConclusionNurses’ the quality of palliative nursing care was in the medium level, and there were two potential categories: the low palliative nursing care quality group and the high palliative nursing care quality group. Nursing managers should take precise measures according to different potential categories of influencing factors to improve the quality of palliative nursing care.